2013
DOI: 10.1186/1471-2458-13-142
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in adolescents with screening-detected celiac disease, before and one year after diagnosis and initiation of gluten-free diet, a prospective nested case-referent study

Abstract: BackgroundCeliac disease (CD) is a chronic disorder in genetically predisposed individuals in which a small intestinal immune-mediated enteropathy is precipitated by dietary gluten. It can be difficult to diagnose because signs and symptoms may be absent, subtle, or not recognized as CD related and therefore not prompt testing within routine clinical practice. Thus, most people with CD are undiagnosed and a public health intervention, which involves screening the general population, is an option to find those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
4
26
1
5
Order By: Relevance
“…This result is in contrast with previous studies showing that dietary restrictions could be difficult to accept and follow, especially during adolescence, a critical period for maintaining the adherence to the GFD [26]. However more recent studies showed similar QOL in adolescents with screening-detected CD as their peers without CD, both at diagnosis and after one year of GFD [27]. Our results should be interpreted with caution, because, as mentioned above, recruited adolescents were strictly adherent to the clinical follow-up and to the diet, therefore possibly reporting a better QOL.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in contrast with previous studies showing that dietary restrictions could be difficult to accept and follow, especially during adolescence, a critical period for maintaining the adherence to the GFD [26]. However more recent studies showed similar QOL in adolescents with screening-detected CD as their peers without CD, both at diagnosis and after one year of GFD [27]. Our results should be interpreted with caution, because, as mentioned above, recruited adolescents were strictly adherent to the clinical follow-up and to the diet, therefore possibly reporting a better QOL.…”
Section: Discussioncontrasting
confidence: 99%
“…This phenomenon observed in most CD studies (6,9,22,26,35,36) could be because of the higher prevalence of the disease in females (3,7,8,18,(37)(38)(39)(40)(41)(42)(43), and also to their greater concern about the disease (7). We effectively observed that more mothers than fathers completed the questionnaire, as also reported by other authors (6,9,17).…”
Section: Discussionmentioning
confidence: 99%
“…Patients detected in screening studies tend to be less symptomatic and up to 51% is without symptoms [38]. The quality of life of screening-detected patients is not significantly different from that of non-celiac controls [39,40], and their quality of life does not benefit from a gluten-free diet [41]. Increased risk of malignancies has frequently been cited as a reason for population screening.…”
Section: Discussionmentioning
confidence: 99%